COMPETENCE-BASED APPROACH IN CHEMISTRY EDUCATION PEDAGOGICAL FOUNDATIONS OF USE - Azhieva, M.B. (SCIENCE and SOCIETY, 2026)
This article analyzes the theoretical foundations, practical application and role of the use of the competency-based approach in chemistry education in developing the necessary competencies in students. The competency-based approach is manifested through the integral connection between theoretical knowledge and practice, the development of practical skills based on experience, problem-based and research-oriented tasks, interdisciplinary integration and the formation of life competencies. According to the results of the pedagogical experiment, this approach significantly increases the student’s analytical thinking, experimental skills and independent research abilities. The data show that the widespread introduction of the competency-based approach in chemistry education is an important factor in increasing educational effectiveness.